Návrh řízeného pohonu paralaktické montáže - Šulc, Dalibor (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2009)
Cílem této práce je rešerše možných pohonů pro paralaktickou montáž a jeho návrh včetně řízení mikrokontrolerem. Práce dále popisuje použitý kaskádní regulátor a metodu pro výpočet nelineárně se měnící polohy. Součástí je také schéma kompletní elektroniky montáže, výpočet a měření odchylek polohy pohonu od teoretické hodnoty. V poslední části je výčet dalších možných problémů, které mohou do fotografování zanášet nepřesnosti.

The aim of this bachelor’s thesis is exploration of facts about drives for parallactic mounting and its design with microprocessor control. In the thesis there is also described the tandem governor and the nonlinear position computing method. One part of this thesis is the complete scheme of mounting electronics, computing and measuring differences between real and theoretic position. The last part of the thesis focuses on the specification of other possible problems, which can bring inaccuracy into taking pictures.
Design of controlled drive for parallactic mounting
Keywords: paralaktická montáž; regulátor; nelineární dráha; pohony; parallactic mounting; governor; nonlinear track; drives